Inflammatory markers and suicidal attempts in depressed patients: A review. (December 2016) - Marini, Stefano; Vellante, Federica; Matarazzo, Ilaria; De Berardis, Domenico; Serroni, Nicola; Gianfelice, Daniela; Olivieri, Luigi; Di Renzo, Fulvia; Di Marco, Anna; Fornaro, Michele; Orsolini, Laura; Valchera, Alessandro; et al.
Major depressive disorder is a chronic and invalidating psychiatric illness and is associated with a greater risk of suicidal behaviors. In recent decades many data have supported a biological link between depressive states and inflammation. Pro-inflammatory cytokines have been found to rise, first of all TNF-α and IL-6. Suicidal behaviors have been consistently associated with increased levels of IL-6 and decreased levels of IL-2. The aim of this review is to investigate the relationship between inflammatory markers in depressed patients with or without suicidal attempts compared to healthy controls.